2017
DOI: 10.1007/s00540-017-2395-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after pediatric liver transplantation: incidence, risk factors, and association with outcome

Abstract: The incidence of AKI after pediatric liver transplantation was 46.2%. Increased preoperative total bilirubin level and increased intraoperative blood loss were independently associated with the development of AKI. AKI was associated with prolonged hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
(49 reference statements)
2
37
2
Order By: Relevance
“…1 Likewise, AKI after pediatric LTx is common with investigators reporting incidence rates ranging from 28% to 57% based on differing criteria used to define AKI. [2][3][4] Consistent with what is shown in other patient groups, AKI after pediatric LTx is associated with a significantly longer duration of mechanical ventilation, an increased hospital length of stay, and an increased risk of mortality. 3,4 Furthermore, AKI is a well-known risk factor for the development of chronic kidney damage and longitudinal studies have demonstrated the presence of renal insufficiency in a substantial proportion of the LTx population, including children.…”
Section: Introductionsupporting
confidence: 77%
“…1 Likewise, AKI after pediatric LTx is common with investigators reporting incidence rates ranging from 28% to 57% based on differing criteria used to define AKI. [2][3][4] Consistent with what is shown in other patient groups, AKI after pediatric LTx is associated with a significantly longer duration of mechanical ventilation, an increased hospital length of stay, and an increased risk of mortality. 3,4 Furthermore, AKI is a well-known risk factor for the development of chronic kidney damage and longitudinal studies have demonstrated the presence of renal insufficiency in a substantial proportion of the LTx population, including children.…”
Section: Introductionsupporting
confidence: 77%
“…AKI is a common and significant complication after liver transplantation (LTx), and is associated with increased mortality, hospital length of stay, utilization of resources, and health care costs [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Although the survival of LTx recipients has improved substantially over the past five decades, mortality rates related to post-LTx AKI and subsequent progressive CKD remain high and are of increasing concern [14,15,28,29,30,31]. The underlying mechanisms for post-LTx AKI appear to be complex and differ from other medical or surgery-associated AKI [11,23,24,25,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested several important factors that influence post-LTx AKI, including hepatic ischemia-reperfusion injury (HIRI) [36,37,38], increased use of high-risk or marginal grafts, and transplantation of liver grafts to sicker patients with higher Model For End-Stage Liver Disease (MELD) score or with more comorbidities [23,39,40,41,42,43,44,45,46,47,48,49,50,51]. In our literature review, the reported incidences are a farrago, having a range between 5% to 94% [10,11,14,15,16,17,18,19,20,21,22,23,24,25,28,29,30,31,32,33,34,35,39,40,41,42,43,44,45,46,47,48,49,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Wide and different ranges of AKI prevalence were reported in several studies, ranging from 17% and 50%, with small patients cohorts, often included in retrospective studies and using different methods to evaluate GFR. [40][41][42] Seventy-seven children, who underwent LTx, were enrolled to evaluate AKI prevalence, comparing the three standardized definitions of AKI based on serum creatinine values, Pediatric RIFLE (pRI-FLE), AKIN, and KDIGO criteria. In particular, pRIFLE detected AKI in 57% of patients, whereas AKIN and KDIGO criteria in only 43% of them.…”
Section: Acute K Idne Y Inj Ury Af Ter Ped Iatri C Lt Xmentioning
confidence: 99%